Geochemistry of the stratiform iron Dunderlandsdalen deposits, Nordland - Rolsted Lie, Kristian (UiT Norges arktiske universitet, 2019)
The Dunderlandsdalen iron district, Northern Norway, hosts a world-class stratiform Fe-mineralization (total tonnage of ~500 Mt at 33% Fe). The iron ore units belong to the Dunderland Formation in the Ramnålia Nappe, which further belongs to the Rødingsfjellet Nappe of the Caledonian Uppermost Allochthon. Hematite and magnetite represent the principal ore minerals and are hosted by amphibolite grade dolomitic and calcitic marble units intercalated with various types of calcareous schists. Although having been described as a world-class iron deposit, it has not been a subject of detailed geochemical studies. In order to determine the controlling mechanisms of hematite and magnetite formation, the present study mainly focuses on investigating the geochemical characteristics of the mineralization and host rocks within a structural framework. In addition, the fluid inclusion study gives insight into the post-ore P-T-X evolution of the studied area. Deformation processes, recrystallization of ore and gangue minerals as well as remobilization of metals during the Caledonian Orogeny affected the ore textures and mineral chemistry of the mineralization. Strain variations in ore bodies and host rocks, which are evident in both macro- and micro-scale, have given rise to different generations of Fe-oxides characterized by significantly different morphologies. The major element characteristics and REE patterns of mineralized samples indicate that the primary mineralizing events involved mixing of a low-temperature hydrothermal source of iron with a detrital component in a rift-related environment. ????13C and ????18O values of gangue carbonates support a deposition under the influence of hydrothermal fluids. Geochemical data, along with the age interval of host rock marble (800 to 730 Ma, Melezhik et al., 2015) have led the author to suggest that the Fe-mineralization of the Dunderland Formation accumulated in glacially and hydrothermally influenced passive margin rift-basins or back-arc basins. Fluid inclusion studies of ...